EFEKTIVITAS KONSUMSI PROTEIN HEWANI (TELUR DAN IKAN) SEBAGAI STRATEGI PENUNTASAN STUNTING - Izah, Nilatul; Desi, Nina Maria (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Nutritional problems in Indonesia result in more than 80 (%) child deaths. Based on the 2022 Indonesian Nutrition Status Study (SSGI) survey, the national prevalence of stunting was 21.6%, Central Java province was 20.8% and in the Central Java region the highest stunting toddler was Brebes Regency, which was 29.1%. Stunting is a condition where a toddler has a length or height that is less than his age. Providing additional food especially for vulnerable groups is one of the supplementation strategies in overcoming nutritional problems. Providing additional food to infants is an effort to meet the nutritional needs of infants so that infants can achieve optimal growth and development.This research is a quantitative study with a cross-sectional design, which aims to determine the effectiveness of consuming animal protein (eggs and fish) for toddlers who are stunted. The study was conducted in May and June by providing food in the form of boiled chicken egg protein and fish for 30 days to 33 respondents. Univariate analysis using frequency distribution and bivariate analysis using Chi-Square. The results showed that there was an increase in nutritional status and a decrease in stunting between before and after receiving the intervention. Statistical tests obtained a p-value of 0.039 which indicated that there was an effect of animal protein (eggs and fish) on stunting.